Optimisation of train speed to limit energy consumption. Issue 10 (3rd October 2022) - Nespoulous, Julien; Soize, Christian; Funfschilling, Christine; Perrin, Guillaume
Abstract : The speed profile of a train plays an important role in energy consumption and resulting costs. The industrial objective of this work is thus to develop a method to reduce the energy consumed by a train over a journey by playing on the driver commands (traction and braking forces) while respecting punctuality constraints. First, a rigid body approach (Lagrangian formalism) is introduced to characterise the dynamics of the train. In particular, the aerodynamic (including the wind effect), traction, and braking forces are taken into account, and a special attention is paid to the vertical and lateral characteristics of the track as they play a key role in the train dynamics. Second, a model for energy consumption and recovery (thanks to dynamic braking) is introduced. Experimental measurements of a high-speed line are then used to estimate the parameters on which the two previous models are based and to validate their predictive capacities. The optimisation problem under constraints is finally solved using an evolutionary algorithm where the constraints are implemented using an augmented Lagrangian formalism. The performance of the proposed method in terms of speed optimisation and energy consumption reduction is compared to measurements associated with commercial trains.